2018
DOI: 10.1021/acs.langmuir.7b03956
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopy of Carbon Nanomembranes from Aromatic Self-Assembled Monolayers

Abstract: Surface-enhanced Raman scattering spectroscopy (SERS) was employed to investigate the formation of self-assembled monolayers (SAMs) of biphenylthiol, 4'-nitro-1,1'-biphenyl-4-thiol, and p-terphenylthiol on Au surfaces and their structural transformations into carbon nanomembranes (CNMs) induced by electron irradiation. The high sensitivity of SERS allows us to identify two types of Raman scattering in electron-irradiated SAMs: (1) Raman-active sites exhibit similar bands as those of pristine SAMs in the finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 59 publications
(122 reference statements)
2
15
0
Order By: Relevance
“…In addition, spurious signals occur which were not assigned due to the low signal to noise ratio. This behavior is consistent with the surface enhanced Raman spectroscopy (SERS) investigation by Zhang et al [61] who showed a gradual loss of Raman signal upon cross-linking of the NBPT SAM. We believe that this low signal is due to the nature of the CNM itself, which is formed from a laterally disordered carbon network [62] that typically shows low Raman crosssections.…”
Section: Terssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, spurious signals occur which were not assigned due to the low signal to noise ratio. This behavior is consistent with the surface enhanced Raman spectroscopy (SERS) investigation by Zhang et al [61] who showed a gradual loss of Raman signal upon cross-linking of the NBPT SAM. We believe that this low signal is due to the nature of the CNM itself, which is formed from a laterally disordered carbon network [62] that typically shows low Raman crosssections.…”
Section: Terssupporting
confidence: 91%
“…We believe that this low signal is due to the nature of the CNM itself, which is formed from a laterally disordered carbon network [62] that typically shows low Raman crosssections. [61] The low Raman scattering cross section of NH2-CNM is a considerable advantage, as it allows to specifically distinguish the specific overlayers in the following experiments without interference.…”
Section: Tersmentioning
confidence: 99%
“…7(c) and (d). Electron irradiation of the SAMs produces carbon-carbon links between neighbouring molecules, 3 which reduce the spatial separation between molecules. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that selfassembled monolayers (SAMs) can be used to form thick, highly ordered molecular carbon systems. [1][2][3] Going beyond the self-assembled monolayers, conjugate organic molecules can lead to new hybrid materials with novel functionalities, which can open new vistas in nanoelectronics and nanotechnology. [4][5][6][7][8] A particular focus has been to create new functional materials for information processing and energy conversion using the self-assembly strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to pure Ag, the TiO 2 -Ag nanocaps exhibited strong absorption in the UV and visible region, as shown in Figure 4. The absorption peaks of the Ag film at about 340 nm and 460 nm came from dipole resonance and quadrupole resonance, which broadened due to the coupling between the quadrupole resonance and the octupole resonance [22]. As the small Ag nanoparticles were almost trapped inside the TiO 2 matrix and there was no exposure to oxygen, the excited electrons transferring from the surface of the Ag nanoparticle to the TiO 2 conduction band remained in the Ag-TiO 2 complex, leading to the increased concentration of free conduction electrons, which broadened the absorption band of the Ag-TiO 2 complex.…”
Section: Resultsmentioning
confidence: 99%